A cell in hand is worth two in the embryo: recent advances in 2-cell like cell reprogramming. (October 2020) - Iturbide, Ane; Torres-Padilla, Maria-Elena
Abstract : Multicellular organisms develop from a single cell, the zygote. This feature is referred to as totipotency. In the mouse, only the zygote and the 2-cell stage embryo display this attribute. Cells resembling the embryonic 2-cell stage blastomeres were identified in embryonic stem (ES) cell cultures as '2-cell-like cells' (2CLCs). This discovery brought the first cellular model with the possibility to investigate some features of the totipotent embryo and the molecular mechanisms regulating totipotency in vitro . In this article, we discuss the latest advancements on the research on 2CLCs, which have uncovered an intricate reprogramming process regulated by proteins as well as metabolites and ncRNAs. These recent findings have shed light on the combinatorial regulation of 2-cell-like cell emergence and the nature of their unique attributes.